Pengaruh Sudut Kemiringan Ayakan Getar (Vibrating Screen) Terhadap Unjuk Kerja Ayakan - Haryono, Achmad; Rubiono, Gatut; Qiram, Ikhwanul (Virtual of Mechanical Engineering Article, 2020)
Sieving is the separation of various mixtures of solid particles that have various sizes of materials using a sieve. The sieving process is also used as a cleaning tool, separating contaminants with different sizes from the raw material. This study aims to determine the effect of the vibrating screen angle on the sieve's performance. The research was conducted by experiment using a flat type vibrating sieve. The angle of the sieve was varied by 0, 5o, 10oand 15o. The vibratory motion of the sieve was varied with the crank method using a rotation of 13.5; 21.3 and 27 rpm. The sieve holes use a screen with mesh sizes number 8, 10 and 12. The sifted sand is 1 kg. Data were collected for the fine and coarse sieve results and the sieving time. The results showed that the angle of the sieve had an effect on the performance of the sieve .